Homeostatic p62 levels and inclusion body formation in CHCHD2 knockout mice. Issue 6 (25th February 2021) - Sato, Shigeto; Noda, Sachiko; Torii, Satoru; Amo, Taku; Ikeda, Aya; Funayama, Manabu; Yamaguchi, Junji; Fukuda, Takahiro; Kondo, Hiromi; Tada, Norihiro; Arakawa, Satoko; Watanabe, Masahiko; et al.
Abstract: Inactivation of constitutive autophagy results in the formation of cytoplasmic inclusions in neurones, but the relationship between impaired autophagy and Lewy bodies (LBs) remains unknown. α-Synuclein and p62, components of LBs, are the defining characteristic of Parkinson's disease (PD). Until now, we have analyzed mice models and demonstrated p62 aggregates derived from an autophagic defect might serve as 'seeds' and can potentially be a cause of LB formation. P62 may be the key molecule for aggregate formation. To understand the mechanisms of LBs, we analyzed p62 homeostasis and inclusion formation using PD model mice. In PARK22-linked PD, intrinsically disordered mutant CHCHD2 initiates Lewy pathology. To determine the function of CHCHD2 for inclusions formation, we generated Chchd2-knockout (KO) mice and characterized the age-related pathological and motor phenotypes. Chchd2 KO mice exhibited p62 inclusion formation and dopaminergic neuronal loss in an age-dependent manner. These changes were associated with a reduction in mitochondria complex activity and abrogation of inner mitochondria structure. In particular, the OPA1 proteins, which regulate fusion of mitochondrial inner membranes, were immature in the mitochondria of CHCHD2-deficient mice. CHCHD2 regulates mitochondrial morphology and p62 homeostasis by controlling the level of OPA1. Our findings highlight the unexpected role of the homeostatic level of p62, which is regulated by a non-autophagic system, in controlling intracellular inclusion body formation, and indicate that the pathologic processes associated with the mitochondrial proteolytic system are crucial for loss of DA neurones.